2017
DOI: 10.1590/1982-7849rac2017160199
|View full text |Cite
|
Sign up to set email alerts
|

Disputas do Estado em Favelas: O Campo Burocrático e o Capital Espacial

Abstract: Resumo Neste artigo nos propomos a analisar como se dão as disputas por capitais pelos agentes do campo burocrático do Estado em ação nas favelas, no contexto da pacificação. Para tal, pautamo-nos na perspectiva teórica de Pierre Bourdieu e realizamos uma pesquisa de campo de inspiração etnográfica em duas favelas cariocas, que contou com observação participante e 91 entrevistas semiestruturadas. Pode-se concluir que as espécies de capital mais valorizadas no campo burocrático do Estado em ação nas favelas são… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The context of favela is important in this study as approximately 12 million Brazilians (6% of the total population) (Instituto Brasileiro de Geografia e Estatística [IBGE] 2010b) live in favelas around the country. Also, it presents a specific dynamic of survival that has been investigated by many scholars in different research areas such as public security and health, consumer behavior, and sociology (e.g., Brulon and Peci 2017;Carvalho 2007;Mattoso and Rocha 2008;Neuhouser 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The context of favela is important in this study as approximately 12 million Brazilians (6% of the total population) (Instituto Brasileiro de Geografia e Estatística [IBGE] 2010b) live in favelas around the country. Also, it presents a specific dynamic of survival that has been investigated by many scholars in different research areas such as public security and health, consumer behavior, and sociology (e.g., Brulon and Peci 2017;Carvalho 2007;Mattoso and Rocha 2008;Neuhouser 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that state agents in action in Rio de Janeiro favelas can be analyzed based on the notion of bureaucratic field of Pierre Bourdieu. This argument is supported by the fact that the state agents relate to each other through disputes and cooperation, as a network of relations between positions (BRULON and PECI, 2017). Therefore, this is also the theoretical perspective adopted in this article.…”
Section: The State As a Field Of Powermentioning
confidence: 76%
“…Situations of conflict between the different state agents acting in the favelas researched have been repeated again and again. Brulon and Peci (2017) show that state agents who work in "pacified" favelas are connected in a network of relationships between positions and can be understood as a 'bureaucratic field,' concept developed by Bourdieu (2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a field, the state is composed of agents that compete among themselves and who seek to produce discourses of legitimacy to justify their dominance, as pointed out by Bourdieu (2011). The state is represented in the favelas by several agents, who present dissensions and have relationships marked primarily by disputes (BRULON and PECI, 2017). In this article, we propose to analyze the discursive strategies of legitimation used by the agents' bureaucratic field of state in action in the favelas, as a way to bring light to the logic behind the disputes in the field.…”
Section: Introductionmentioning
confidence: 99%